Ultrastable atomically precise chiral silver clusters with more than 95% quantum efficiency - Han, Zhen (Sci Adv, 2020)
Monolayer-protected atomically precise silver clusters display low photoluminescence (PL) quantum yield (QY) and susceptibility under ambient conditions, and their chiroptical activities also remain underdeveloped. Here, we report enantiomers of an octahedral Ag(6) cluster prepared via one-step synthesis using designed chiral ligands at ambient temperature. These clusters exhibit a highest PLQY (300 K) >95.0% and retain their structural integrity and emission up to 150°C in air. Atomically precise structural determination combined with photophysical and computational analysis revealed that thermally activated delayed fluorescence, observed in silver cluster systems, is responsible for the high PLQY, which combines chirality in excited states to generate strong circularly polarized luminescence. These unprecedented findings open up horizons of investigation of monolayer-protected silver clusters for future luminescence applications.